A new species of the eulimid genus Pelseneeria Koehler & Vaney, 1908 (Mollusca: Gastropoda) from Staten Island, Argentina - Pastorino, Roberto Santiago Guido (2001)
A new species of the eulimid genus Pelseneeria is described from Punta Laserre (63°52′49″W, 54°45′06″S), Staten Island, Argentina. Pelseneeria sudamericana, sp. nov. lives attached to the test of the echinoid Pseudechinus magellanicus (Philippi, 1857). Adults, juveniles, and egg capsules of the new species are illustrated, described, and compared with other living species of the same genus. This is the first report of the genus Pelseneeria in South America, and the first record of a eulimid as a parasite of Pseudechinus magellanicus.